Reactions of o-aminothiophenol and o-aminophenyl disulfide with itaconic anhydride and (-)-dimenthyl itaconate: access to enantiomerically pure 1,5-benzothiazepines and benzothiazolyl-2-methylacrylic acid - Baag, Md. Merajuddin; Sahoo, Manoj Kumar; Puranik, Vedavati G.; N. P. Argade (Synthesis-Stuttgart, 2007)
{A facile chemo- and regioselective reactions of o-aminothiophenol (o-ATP) with itaconic anhydride is described. 1,5-Benzothiazepinyl-3-acetic acid is obtained in 81% yield via the exclusive Michael type addition of the thiol unit from o-ATP to the carbon-carbon double bond in itaconic anhydride followed by an intramolecular anhydride ring opening with an amine unit. The moderately stereoselective Michael type addition of the thiol unit from o-ATP to (-)-dimenthyl itaconate to obtain a mixture of diastereomers in a 7:3 ratio in 82% yield has been demonstrated. The reductive sulfur-sulfur bond cleavage in the dicarboxylic acid, 2({2-[2-(3-carboxybut-3-enoylamino)phenyidisulfanyl]phenylcarbamoyl\
Keywords: Magnetic nanoparticles; magnetic properties; spin glasses